A cross-firm analysis of the impact of corporate governance on the East Asian financial crisis - Mitton, Todd (Journal of Financial Economics, 2002)
In a sample of 398 firms from Indonesia, Korea, Malaysia, the Philippines, and Thailand, firm-level differences in variables related to corporate governance had a strong impact on firm performance during the East Asian financial crisis of 1997–1998. Significantly better stock price performance is associated with firms that had indicators of higher disclosure quality (ADRs and auditors from Big Six accounting firms), with firms that had higher outside ownership concentration, and with firms that were focused rather than diversified. The results suggest that individual firms have some power to preclude expropriation of minority shareholders if legal protection is inadequate.